Application of nanofluid to improve the thermal performance of horizontal spiral coil utilized in solar ponds: Geometric study. (July 2018) - Khodabandeh, Erfan; Safaei, Mohammad Reza; Akbari, Soheil; Akbari, Omid Ali; Alrashed, Abdullah A.A.A.
Abstract: Today, one of the most common methods for heat extraction from the solar ponds is using spiral piping system. In this study, effects of nanofluid concentrations and different cross-sections of tube on thermal performance of horizontal spiral-coil in laminar fluid flow are investigated numerically. Water-graphene nanoplatelet/platinum hybrid nanofluid with 0.02, 0.06 and 0.10% volume concentration has used as working fluid. Simulations are performed for different mass flow rates between 0.0005 and 0.005 kg/s. Different shapes including rectangle, elliptic, trapezoid and circle are selected as tube cross-sections. Uniform temperature and velocity distributions with several mass flow rates are applied to geometry at inlet and constant wall temperature as boundary conditions. The results show that variations of average Nusselt number in lower mass flow rates is not dependent to the shape of flow cross-section. By increasing the nanoparticles concentration, the highest Nusselt number belongs to tube with elliptical cross-section. Surfaces with angular corners create greater velocity variations in comparison with surfaces with curved corners and this behavior leads to higher pressure loss as well as more pumping power. Also, by increasing mass flow rate, the heat transfer between hot surfaces and cooling fluid is enhanced. The highest and lowest values of outlet temperature are reported for fluid with highest solid nanoparticle volume concentration and distilled water, respectively. Among the considered mass flow rates in φ = 0.06 and 0.10%, mass flow rate of 0.002 kg/s has the highest thermo-fluid efficiency. Graphical abstract: Image 1 Highlights: Nanofluid study shows efficiency improvement in solar ponds. Different geometries, mass flow rates and nanoparticle concentrations have considered. Increasing φ, highest Nusselt number belongs to tube with elliptical cross-section. Surfaces with angular corners cause higher pressure loss.